Neuromyelitis optica spectrum disorders: Comparison according to the phenotype and serostatus. Issue 3 (June 2016) - Sepúlveda, Maria; Armangué, Thaís; Sola-Valls, Nuria; Arrambide, Georgina; Meca-Lallana, José E.; Oreja-Guevara, Celia; Mendibe, Mar; Alvarez de Arcaya, Amaya; Aladro, Yolanda; Casanova, Bonaventura; Olascoaga, Javier; Jiménez-Huete, Adolfo; et al.
Abstract : Objective: To (1) determine the value of the recently proposed criteria of neuromyelitis optica (NMO) spectrum disorder (NMOSD) that unify patients with NMO and those with limited forms (NMO/LF) with aquaporin-4 immunoglobulin G (AQP4-IgG) antibodies; and (2) investigate the clinical significance of the serologic status in patients with NMO. Methods: This was a retrospective, multicenter study of 181 patients fulfilling the 2006 NMO criteria (n = 127) or NMO/LF criteria with AQP4-IgG (n = 54). AQP4-IgG and myelin oligodendrocyte glycoprotein immunoglobulin G (MOG-IgG) antibodies were tested using cell-based assays. Results: Patients were mainly white (86%) and female (ratio 6.5:1) with median age at onset 39 years (range 10–77). Compared to patients with NMO and AQP4-IgG (n = 94), those with NMO/LF presented more often with longitudinally extensive transverse myelitis (LETM) ( p < 0.001), and had lower relapse rates ( p = 0.015), but similar disability outcomes. Nonwhite ethnicity and optic neuritis presentation doubled the risk for developing NMO compared with white race ( p = 0.008) or LETM presentation ( p = 0.008). Nonwhite race (hazard ratio [HR] 4.3, 95% confidence interval [CI] 1.4–13.6) and older age at onset were associated with worse outcome (for every 10-year increase, HR 1.7, 95% CI 1.3–2.2). Patients with NMO and MOG-IgG (n = 9) had lower female:male ratio (0.8:1) and better disability outcome than AQP4-IgG-seropositive or double-seronegative patients ( p < 0.001). Conclusions: In patients with AQP4-IgG, the similar outcomes regardless of the clinical phenotype support the unified term NMOSD; nonwhite ethnicity and older age at onset are associated with worse outcome. Double-seronegative and AQP4-IgG-seropositive NMO have a similar clinical outcome. The better prognosis of patients with MOG-IgG and NMO suggests that phenotypic and serologic classification is useful.